Role salience and satisfaction in working adults: a contribution to the individuals’ well-being - Lima, Rosário; Gaspar, Pedro (REOP - Revista Española de Orientación y Psicopedagogía, 2021)
ABSTRACT A study about role salience in the counselling and career management context with an adult sample revealed the tendency for the individuals to place more importance in other roles beyond those they tend to spend more time and energy with: work and family. The aim of this research is to present more results that confirm this trend, in different organizational contexts, and also the satisfaction with the occupational, family and leisure life roles. The study samples included working adults, ranging from 60 to 116 participants, and the instruments used were the Salience Inventory and the Life Roles Satisfaction Scale. The results corroborate the referred trend and reveal higher levels of satisfaction with other activities than with the occupational one, and correlations between role salience and satisfaction with the life roles. Therefore, it should be considered strategic by the organizations to implement policies aiming to facilitate the balance between the different roles played by their employees. Noteworthy are the interventions in counselling and career management and the increasingly frequent use of remote work. Some considerations are made on the importance of helping individuals to deal with their levels of satisfaction and well-being in the current competitive, unpredictable and unknown labour market. RESUMEN Con base en un estudio sobre la relevancia de los roles con una muestra de adultos que solicitaron ayuda en el contexto de asesoramiento y gestión de carrera, se encontró una tendencia a dar más y más importancia a los roles que no sean los que generalmente los individuos tienden a gastar más de su tiempo y energía: el trabajo y la familia. Este estudio tiene como objetivo presentar más resultados que confirmen esta tendencia, en diferentes contextos organizacionales, y también la satisfacción obtenida con los roles de vida profesional, familiar y de ocio. Las muestras en estudio incluyeron adultos trabajadores, cuyos totales oscilaron entre 60 y 116 participantes, y los instrumentos utilizados fueron el Inventario de Saliencia de Actividades y la Escala de Satisfacción con los Roles Vitales. Los resultados corroboran la tendencia mencionada y revelan mayores niveles de satisfacción con otras actividades que la profesional, y correlaciones entre la relevancia de los roles y la satisfacción con los roles de vida. Por consiguiente, debe considerarse estratégico que las organizaciones implementen medidas destinadas a facilitar el equilibrio entre los diferentes roles desempeñados por sus trabajadores. Cabe destacar las intervenciones en asesoramiento y gestión de la carrera y el uso cada vez más frecuente del trabajo remoto. Se hacen algunas consideraciones sobre la importancia de ayudar los individuos a lidiar con sus niveles de satisfacción y bienestar en el actual mercado laboral competitivo, impredecible y desconocido.